The effect of corrective exercises on the thoracic kyphosis and lumbar lordosis of boy students - Ahmet Gökhan Yazıcı; Mohsen Mohammadı (Selcuk University, 2017)
Corrective actions are a branch of applied science and include the identification, education, prevention, correction of wrong habits of body and motor abnormalities. The purpose of this study was to assess the effectiveness of eight-week corrective exercises on boy students with kyphosis and lordosis. 40 boy students were randomly divided into two groups with 20 subjects in each group including experimental group and control group. The experimental groups performed the corrective exercises for eight weeks with three sessions a week. Pre and post measures of kyphosis and lordosis curve were obtained using a spinal mouse. Measuring of variables was performed before (pre-test) and after (post-test) the protocol. Eight weeks corrective exercise period can be resulted in the reduction of kyphosis angle and lordosis angle boy student. In general, implementation of corrective exercise in patients with kyphosis and lordosis was a successful plan.